Effects of para-aminobenzoic acid (PABA) form and administration mode on PABA recovery in 24-hour urine collections - Sharma, R.; Joy, R.; Boushey, Carol; Ferruzzi, M.; Leonov, A.; McCrory, M. (Elsevier, 2014)
Para-aminobenzoic acid (PABA) has long been used as an objective measure to assess completeness of 24-hour urine collections. However, pharmaceutical-grade PABA for human ingestion is not available in the United States. An alternative, the potassium salt of PABA, aminobenzoate potassium, can be obtained for clinical use, although it has not yet been validated in this role. Both PABA and aminobenzoate potassium can be directly ingested in their tablet or capsule forms or added to food before consumption. Our aim was to investigate the effect of form (PABA vs aminobenzoate potassium) and administration mode (directly ingested as a tablet/capsule vs added to food) on urinary PABA recovery levels. Twenty healthy participants underwent 3 test days separated by two 24-hour wash-out periods. Three test conditions, one on each test day, were investigated in randomized order: PABA tablet, aminobenzoate potassium capsule, and PABA or aminobenzoate potassium in food. Ingestion of each dose was supervised and participants performed the 24-hour urine collections while free-living. The 24-hour urine collections were analyzed for PABA recovery (%R) levels using a colorimetric assay. Recoveries 85% to 110% were deemed complete and those >110% were reanalyzed by high pressure liquid chromatography and mass spectrometry. Only complete collections (>85%R) were included in analyses. The recovery for the PABA tablet, aminobenzoate potassium capsule, and PABA/aminobenzoate potassium in food were similar at 98.8%R±2.0%R, 95.1%R±2.3%R, and 93.2%R±2.1%R, respectively, and did not differ significantly. These results suggest that aminobenzoate potassium may be used as an alternative to PABA for assessing the completeness of 24-hour urine collections and to track compliance with consuming provided diets in community-dwelling studies.